MOLECULAR CHARACTERIZATION OF BEGOMOVIRUS INFECTING ABUTILON GLAUCUM IN SOUTH GUJARAT REGION - RISHEE KALARIA; M. K. MAHATMA; LALIT MAHATMA (The Bioscan, 2013)
Weeds are potential sources of primary inoculum of viruses and play an important role in their persistence and spread. During the rainy season of 2010 - 2012, several plants of Abutilon glaucum in and around Navsari Agricultural university have been found with vein yellowing symptoms. In severe cases, the chlorosis extends into interveinal areas, resulting in complete yellowing of the leaves. Leaf samples from different plants showing severe symptoms were collected and tested for the presence of begomoviruses using PCR assay with the sets of degenerate primers designed to amplify part of the DNA-A strand. A PCR product of the expected sizes (750bp) was obtained with all infected samples. A 696 bp sequence of DNA-A molecule was obtained and submitted to GenBank (Accession Nos. JX258326). The highest nucleotide identity of 93% (BLASTn, NCBI) was obtained with Kenaf leaf curl virus-[India:Kaisarganj:2007]. The phylogenetic reconstruction were done by comparing sequence with other begomovirus AV1 gene. A survey of literature revealed that there is no record of a viral affecting this weed and, therefore, this is the first report of a viral disease affecting this weed plant.